Cryptocurrency system as a digital currency in Islamic economics - Zulkarnain; Wargo; Kuswanto (Zabags Qu Publish, 2025)
The rise of digital technologies has propelled cryptocurrency as a global financial innovation offering efficiency, transparency, and decentralized transactions. Its adoption, however, remains contentious in Indonesia, where regulations restrict its use as legal tender, and in Islamic economics, where concerns persist over speculative behavior, gharar, and maysir. This study aims to examine how cryptocurrency systems function as digital currencies and assess their compatibility with Islamic economic principles. Employing a qualitative phenomenological approach, data were gathered through interviews, observation, and documentation, then validated via triangulation. Findings indicate that cryptocurrency is predominantly used as a speculative investment rather than a medium of exchange, driven by anticipated economic gains amid persistent price volatility and regulatory uncertainty. From a Sharia perspective, most informants view its use as problematic, though some support conditional acceptance subject to governance aligned with maqasid al-sharia. This study contributes to Islamic economics by integrating users’ empirical experiences with normative analysis and offers practical implications for regulators and Islamic financial institutions in formulating policies for digital assets in the contemporary era